2012
DOI: 10.1007/s00213-012-2706-0
|View full text |Cite|
|
Sign up to set email alerts
|

Histamine- and haloperidol-induced catalepsy in aged mice: differential responsiveness to l-DOPA

Abstract: The mouse histamine-induced catalepsy, unlike haloperidol-induced one, displays the same pattern of age dependency as PD. These findings support an involvement of histamine in the PD pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…Since the mean lifespan for these animals was approximately 750 days (12), these animals were considered as young and old. Rats were housed as described previously (13). Animals were randomly divided into groups of seven animals.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the mean lifespan for these animals was approximately 750 days (12), these animals were considered as young and old. Rats were housed as described previously (13). Animals were randomly divided into groups of seven animals.…”
Section: Animalsmentioning
confidence: 99%
“…CycloSOM at the doses of 0.2, 1.0, 5.0, and 10.0 µg and histamine at the doses of 1.0 and 10.0 µg were administered intracerebroventricularly (i.c.v.). The doses were selected according to the previous studies (8,13).…”
Section: Drugsmentioning
confidence: 99%
“…For example, Tournissac et al (2016) demonstrated potentiated cold-induced tau phosphorylation in old mice, a mechanism that may contribute to the susceptibility of older populations to develop Alzheimer disease. Nigrostriatal dopaminergic neurons of older mice appeared more sensitive to neurotoxicity (Thiruchelvam et al, 2003) and to histamine-induced cataplexy and less responsive to L-DOPA (Ionov and Severtsev, 2012), which sheds further light on the mechanisms involved in Parkinson’s disease.…”
Section: Introductionmentioning
confidence: 99%
“…In direct experiments, exogenous histamine produced selective degeneration of dopaminergic neurons in rat substantia nigra [24]; in essence, histamine is the only brain factor that is found to induce the main histopathological feature of iPD. Besides, in mice, histamine can exert catalepsy that is antagonized by levodopa [25][26][27]. Alternatively, histamine H 1 receptor antagonists can elevate dopamine levels in rat neostriatum and nucleus accumbens [28]; these drugs also attenuate cataleptic response induced by haloperidol [23,29] and a few other cataleptogens [29].…”
Section: Introductionmentioning
confidence: 99%